The detector control system of ALICETRD - Busch, Oliver (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2013)
The ALICE Transition Radiation Detector (TRD) is one of the largest TRDs ever built. The TRD Detector Controls (DCS) System was conceived to maintain safe detector conditions and allow failsafe, reliable and consistent operation of such a highly complex detector. We present the design and implementation of TRD DCS with emphasis on practical aspects of detector operation at the Large Hadron Collider.